Merancang Pembelajaran Interaktif Mata Kuliah Organisasi Komputer sebagai Media Pembelajaran Online bagi Mahasiswa Akademi Teknologi AUB Surakarta - Agus Nugroho; Galih Wisnu Wardhana; Robby Rachmatullah (Journal of Indonesian Science Economic Research, 2020)
The computer organization course is a basic subject that must be in the Electronics Engineering Study Program at the AUB Surakarta Institute of Technology. The computer organization course has a weight of 2 credits. This course must be taken for Electrical Engineering students because it is the basis of advanced courses in the Electronics Engineering Study Program. Currently, the method of learning computer organizations in the Electronics Engineering Study Program of the AUB Surakarta Institute of Technology is mostly carried out using lectures, discussions, demonstrations, dissemination, and practicum methods. This method is quite effective, but not enough if the desire to learn requires students to be more active and independent. The learning process cannot be shortened to save time, this is because the lecturer must always provide instructions to the students. Of course, it is less effective in mastering computer organization courses, therefore the use of interactive multimedia-based learning media is important to be used as a solution to reduce obstacles in the learning process. The development of interactive multimedia-based learning media uses the development of Borg and Gall's Research and Development (R&D) development model in Sukmadinata (2007). The development of reason refers to the development of the Borg and Gall model in Sukmadinata as follows: (1) having a rational stage in the development of instructional media; (2) in this model, revisions are made at each stage after testing, so that the media is more developed.